Synthesis of phosphorus analogs of TSAO-T. Issue 36 (6th September 2018) - Moura, Marina; Josse, Solen; Postel, Denis
Abstract: Phosphorus Analogs of TSAO bearing an oxaphospholene ring instead of an oxathiole dioxide ring at C-3′ position were prepared. Strategy developed previously on saccharidic moiety was used with introduction of an electron withdrawing α group neighboring the phosphorus atom. Biological evaluation on both HIV-1 and HCV showed that these compounds have no activity. Graphical abstract: Image 1